2014
DOI: 10.1117/12.2037385
|View full text |Cite
|
Sign up to set email alerts
|

Variable temperature carrier dynamics in bulk (In)GaAsNSb materials grown by MOVPE for multi-junction solar cells

Abstract: III-V multi-junction solar cells are typically based on a triple-junction design that consists of an InGaP top junction, a GaAs middle junction, and a bottom junction that employs a 1 -1.25 eV material grown on GaAs substrates. The most promising 1 -1.25 eV material that is currently under extensive investigation is bulk dilute nitride such as (In)GaAsNSb lattice matched to GaAs substrates. The approach utilizing dilute nitrides has a great potential to achieve high performance triple-junction solar cells as r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…[14,15] Meanwhile, high densities of background impurities make the material quality even worse. [16,17] As for the solar cell application, the peak EQE of the GaInNAs sub-cell grown in MOCVD by Wu et al was 35%. [18] By using TEGa as the Ga source, Dimroth et al reported a GaInNAs solar cell with a peak EQE of 70% at 600 nm and an average EQE of 46% in the expected working range (880-1200 nm).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14,15] Meanwhile, high densities of background impurities make the material quality even worse. [16,17] As for the solar cell application, the peak EQE of the GaInNAs sub-cell grown in MOCVD by Wu et al was 35%. [18] By using TEGa as the Ga source, Dimroth et al reported a GaInNAs solar cell with a peak EQE of 70% at 600 nm and an average EQE of 46% in the expected working range (880-1200 nm).…”
mentioning
confidence: 99%
“…The ECV test of the GaInNAs layers shows that the p-type doping concentration reduces from 1.2 × 10 17 cm −3 (H 2 ambient) to 7.4 × 10 16 cm −3 (N 2 ambient), indicating the concentration reduction of carbon, which is considered as the p dopant in GaInNAs. [16,17] This can be explained by the reduction of CH • 3 and CN • impurities in GaInNAs. The reduction of CH • 3 is a result of a lower DMHy flux, while the reduction of CN • impurities in GaIn-NAs may be caused by the relatively higher incorporation efficiency of NH • 2 compared to that of HCN.…”
mentioning
confidence: 99%